Classification and regression models of audio and vibration signals for machine state monitoring in precision machining systems. (October 2021) - Han, Seulki; Mannan, Nasir; Stein, Daryl C.; Pattipati, Krishna R.; Bollas, George M.
Highlights: Audio and vibration signals transformed for machine state inference Machine learning algorithms enable precise machine state prediction Integrated tool-chain shared in open-source software 100% classification and very accurate regression feasible with minimum hardware investment Abstract: We present a data-driven method for monitoring machine status in manufacturing processes. Audio and vibration data from precision machining are used for inference in two operating scenarios: (a) variable machine health states (anomaly detection); and (b) settings of machine operation (state estimation). Audio and vibration signals are first processed through Fast Fourier Transform and Principal Component Analysis to extract transformed and informative features. These features are then used in the training of classification and regression models for machine state monitoring. Specifically, three classifiers (K-nearest neighbors, convolutional neural networks and support vector machines) and two regressors (support vector regression and neural network regression) were explored, in terms of their accuracy in machine state prediction. It is shown that the audio and vibration signals are sufficiently rich in information about the machine that 100% state classification accuracy could be accomplished. Data fusion was also explored, showing overall superior accuracy of data-driven regression models.